PENGARUH GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PG KREBET BARU MALANG - Andina Chaterine Mangkung (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to determine the significance of the influence of leadership style consisting of directive leadership, supportive leadership, participative leadership, and the achievement oriented leadership on employee productivity in PG Krebet Baru Malang and to know the leadership style that has the most dominant influence on work productivity in PG Krebet New Malang. Type of research used is explanatory research. The subjects of this study were 50 PG employees. Krebet Baru Malang. The analysis technique used is Multiple Linear Regression Analysis using F Test and T Test as Hypothesis Test.Instrument test results both validity and reliability test against 50 respondents obtained valid and reliable results. Leadership style consisting of directive leadership (X1), supportive leadership (X2), participative leadership (X3), and the achievement oriented leadership (X4) have a significant influence on work productivity (Y) PG employees. Krebet Baru Malang. The supportive leadership (X2) style has the most influence on employee work productivity.Kata Kunci: Gaya Kepemimpinan, Produktivitas Kerja